The Pandemic EVIDENCE Collaboration Pillar 1: diagnostics and transmission - Conly, J; Plüddemann, A; Jefferson, T; Rosca, C; Heneghan, C (Kellogg College, University of Oxford, 2024)
The COVID-19 pandemic starkly revealed a lack of high-quality evidence for non-pharmacological interventions (NPIs). The evidence produced to support the optimal deployment of NPIs to reduce transmission of SARS-CoV-2 was often of poor quality, and decisions were made without considering the wealth of previous research on respiratory virus transmission from human challenge studies. Respiratory virus infections cause illnesses varying from the “common cold” to invasive pneumonitis with multisystem involvement with severity dependent on the host-virus-immune response interaction. Despite the learnings from the recent pandemic, significant gaps remain in our understanding of the diagnosis of acute respiratory viral infections and their sequelae, the modes of transmission, and how to effectively synthesise the existing evidence from the past 70 years of research on respiratory viruses. It is crucial to examine further the evidence on how common respiratory viral agents are transmitted. The transmission dynamics to allow for a replication-competent virus to move from a reservoir to a susceptible host and establish an invasive infection is complex and it is likely multiple modes of transmission exist from direct reservoir-to-host (contact, droplet deposition, transplacental) and indirect reservoir-to-intermediary-to- host (vehicle-borne, foodborne, waterborne, and airborne) routes. To enhance our understanding of both diagnostics and transmission, we need to characterise viral entry and attachment, viral load dynamics, duration of virus infectivity both inside and outside the host, duration of viral nucleic acid shedding using molecular testing, the role of whole genome sequencing, and factors that may affect the duration of infectivity and transmission. There are still uncertainties surrounding current testing strategies and their connection to NPIs, as well as fundamental issues such as the accuracy of symptom reporting during acute respiratory infections. The importance of animal-to-animal, human-to-animal and human-to-human challenge studies in expanding our knowledge of the transmission of respiratory viruses cannot be overstated.